2018
DOI: 10.1111/pbr.12620
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci associated with rice black‐streaked dwarf virus disease and its insect vector in rice (Oryza sativa L.)

Abstract: Rice black‐streaked dwarf virus disease (RBSDVD), transmitted by small brown planthopper (SBPH, Laodelphax striatellus), causes serious loss in rice production. Breeding resistant cultivars are one of the most effective strategies to control the virus disease and its vector. By both natural inoculations in the field and modified seedling‐box screening test in the glasshouse, an indica variety WR24 showed high resistance to RBSDVD and SBPH. An F2:3 population consisting of 153 lines derived from a cross between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…To ensure effective and accurate scoring of all test materials, the seedlings of the susceptible control were allowed to die based on the bulk seedling test [ 52 ]. The resistance to SBPH of all test materials was assessed using a slightly modified seedling box screening test described by Xu [ 53 ]. In this test, approximately 30 seeds from each individual plant were planted in a soil-filled plastic pot measuring 5.8 cm × 6.0 cm, with a hole at the bottom.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure effective and accurate scoring of all test materials, the seedlings of the susceptible control were allowed to die based on the bulk seedling test [ 52 ]. The resistance to SBPH of all test materials was assessed using a slightly modified seedling box screening test described by Xu [ 53 ]. In this test, approximately 30 seeds from each individual plant were planted in a soil-filled plastic pot measuring 5.8 cm × 6.0 cm, with a hole at the bottom.…”
Section: Methodsmentioning
confidence: 99%
“…Three QTLs related to SBPH resistance (qSBPH2b, qSBPH3d, and qSBPH12a) were identified on chromosomes 2, 3, and 12 in the cultivar Mudgo, respectively (Duan Karim andPathak 1982 et al 2009). Additional QTLs for SBPH resistance were identified, including qSBPH2, qSBPH3, qSBPH8, and qSBPH11 on chromosome 2, 3, 8, and 11 in Kasalath, respectively; qSBPH2, qSBPH3, qSBPH5, qSBPH7, and qSBPH11 on chromosome 2, 3, 5, 7, and 11 in N22, respectively; qSBPH3d, qSBPH7a, and qSBPH12b on chromosome 3, 7, and 12 in Pf9279-4, respectively; qSBPH1, qSBPH5, qSBPH8, and qSBPH9 on chromosome 1, 5, 8, and 9 in 9194, respectively; and qSBPH5, qSBPH7, and qSBPH10 on chromosome 5, 7, and 10 in WR24, respectively (Duan et al 2010, Wang et al 2013b, Sun et al 2017, Xu et al 2018b, Table 1). Although individual QTLs have only small effects on SBPH resistance, it is useful to apply multiple QTLs for SBPH resistance breeding.…”
Section: Insect Resistance Gene Mappingmentioning
confidence: 99%
“…To facilitate the use and transfer of host resistance in breeding programmes, recent QTL mapping or genome-wide association studies have identified genomic regions associated with RBSDV resistance and linked DNA markers (Feng et al, 2019;Xiao et al, 2019). Several QTLs on different chromosomes have been identified in japonica cultivar Koshihikari, and indica cultivars Minghui 63, WR24, Tetep, IR36, and 9194 (Wang et al, 2010;Li et al, 2013;Zhou et al, 2015a;Zhang et al, 2016;Sun et al, 2017;Xu et al, 2018).…”
Section: Is E a S E Manag Ementmentioning
confidence: 99%